Learning management systems and pedagogical innovation: Evidence from academic staff in China - Lee, Bih Ni; Li Liang; Cheng Haibao (RSIS International, 2025)
This study explores the intersection of Learning Management Systems (LMS) and pedagogical innovation among academic staff in China through a synthesis-method approach. Drawing on primary data from both quantitative surveys and qualitative interviews, the research identifies key trends in LMS adoption, usage patterns, and institutional support mechanisms that influence digital teaching practices. Quantitative metrics highlight the frequency of LMS integration and its perceived effectiveness, while qualitative insights reveal educators’ motivations, challenges, and adaptation strategies. The findings underscore the importance of aligning technological tools with pedagogical goals and institutional culture to foster meaningful innovation in Chinese higher education.